ANALISIS KARAKTERISTIK KANDUNGAN KOPI BENING (CLEAR COFFEE) KABUPATEN BANYUWANGI - Megandhi Gusti Wardhana; M. Sabiq Irwan (Universitas Muhammadiyah Mataram, 2020)
This research aims to find out the effect of preliminary treatment (roasted light roasting 190°C, medium roasting 195°C and dark roasting 200°C) and distillation method (water distillation and coffee extract) on the characteristics of clear coffee and provide benefits to know the characteristics of quality contained in the content of clear coffee. The method used is a distillation method that is carried out for 1 hour to be able to produce a clear copy that was previously done extras with the grinder Latina600N, Cloth Filter and Moka Pot and these results will be tested proximate and organoleptic test and then calculated variance analysis. The characterization of clear coffee in the testing of pH levels, protein content, moisture content, ash content, fat content, and caffeine content resulted that the dark roasting treatment (195°C-200°C) had the highest percentage value with low caffeine levels and roasting temperature treatment of 195°C-200°C had the highest favored level by using the commonly used Latina 600N grinder cafe-café coffee in general, and based on the results of roasting temperature variant 195°C-200°C has no noticeable effect with other temperature treatment as well as grinders used.